ANALYZING THE IMPACT OF REDUCING FOOD LOSSES OF RICE ON FOOD SECURITY IN BENIN - Amoussouhoui, Rico; Akpa, Kuassi Auxence Aristide; Nkhata, Smith G.; Banout, Jan (Economics of Agriculture, 2023)
A substantial amount of rice grains is lost along the value chain, contributing to food insecurity among farming households in Benin. While food losses are inevitable along the value chain, it is imperative to determine the minimum acceptable loss for rice. This study aims to quantify the food losses of rice and determine its effect on food security using the Food Consumption Score (FCS) and Linear model. The results show a positive effect of a low loss rate on the FCS. In addition, a low loss rate increases the probability of FCS by 82.4 for the overall rice farmers and 83.7 for the efficient rice producers. Thus, reducing the loss rate throughout the food chain to a maximum of 10% would increase the amount of local rice on the market and allow producers to achieve food security. The study recommends sensitizing stakeholders along the rice value chain on strategies or technologies to reduce losses.